Arabidopsis acyl‐CoA‐binding protein ACBP1 participates in the regulation of seed germination and seedling development. (1st March 2013) - Du, Zhi‐Yan; Chen, Mo‐Xian; Chen, Qin‐Fang; Xiao, Shi; Chye, Mee‐Len
Summary A family of six genes encoding acyl‐CoA‐binding proteins (ACBPs), ACBP1–ACBP6, has been characterized in Arabidopsis thaliana. In this study, we demonstrate that ACBP1 promotes abscisic acid (ABA) signaling during germination and seedling development. ACBP1 was induced by ABA, and transgenic Arabidopsis ACBP1‐over‐expressors showed increased sensitivity to ABA during germination and seedling development, whereas the acbp1 mutant showed decreased ABA sensitivity during these processes. Subsequent RNA assays showed that ACBP1 over‐production in 12‐day‐old seedlings up‐regulated the expression of PHOSPHOLIPASE Dα1 (PLDα1) and three ABA/stress‐responsive genes: ABA‐RESPONSIVE ELEMENT BINDING PROTEIN1 (AREB1), RESPONSE TO DESICCATION29A (RD29A) and bHLH‐TRANSCRIPTION FACTOR MYC2 (MYC2). The expression of AREB1 and PLDα1 was suppressed in the acbp1 mutant in comparison with the wild type following ABA treatment. PLDα1 has been reported to promote ABA signal transduction by producing phosphatidic acid, an important lipid messenger in ABA signaling. Using lipid profiling, seeds and 12‐day‐old seedlings of ACBP1‐over‐expressing lines were shown to accumulate more phosphatidic acid after ABA treatment, in contrast to lower phosphatidic acid in the acbp1 mutant. Bimolecular fluorescence complementation assays indicated that ACBP1 interacts with PLDα1 at the plasma membrane. Their interaction was further confirmed by yeast two‐hybrid analysis. As recombinant ACBP1 binds phosphatidic acid and phosphatidylcholine, ACBP1 probably promotes PLDα1 action. Taken together, these results suggest that ACBP1 participates in ABA‐mediated seed germination and seedling development.